Differential diagnosis of vascular cognitive impairment - Olga O. Martynova; Vladimir V. Zakharov (ZAO "Consilium Medicum", 2022)
Background. Vascular cognitive impairment (VCI), аccording to world statistics, is the second most common cause of cognitive impairment after Alzheimer's disease (AD). Differential diagnosis between the two most common nosological forms of cognitive impairment is not always simple and is based on the clinical characteristic, neuropsychological and neuroradiological features of the disease. Aim. To present a differential diagnosis between VCI and AD using the example of a clinical case of vascular mild cognitive impairment. Materials and methods. A 68-year-old female patient with mild cognitive impairment underwent a neuropsychological testing: the Mini-mental state exam, Frontal assessment battery, the MoCA-test, the Clock-Drawing Test, the 12 Words test, Verbal Association Technique (literal and categorical), The Trail making test (A and B), The digit symbol substitution test, The Boston naming test (40 images), EXIT-25, Beck Depression Scale, Hospital anxiety and depression scale; neuroimaging magnetic resonance imaging in T1, T2, FLAIR, DWI, SWI sequence. Results. On the basis of clinical data, the results of neuropsychological testing and neuroimaging, the differential diagnosis with AD, the patient was diagnosed with vascular mild cognitive impairment. Nootropic therapy (choline alfoscerate) was prescribed and recommendations on risk factors correction were given. Conclusion. The article describes a patient with mild VCI. This case study discusses the main differences between AD and VCI that can be used as a basis for differential diagnosis. The features of cognitive impairments in VCI and AD are described, including the predominance of attention impairment, an executive function disorder in VCI and an impairment of memory progressing according to the Ribots law in AD. Differences in visuospatial skills and language in VCI and AD are discussed. The most reliable neuroradiological signs of cerebrovascular diseases are described.